Pentadbiran tanah di Sarawak : satu tinjauan di bahagian Samarahan - Kram, Haji Saini (University Malaysia Sarawak, UNIMAS., 2000)
The topic of this study is 'the Administration of Land in Sarawak'. A case study on Samarahan Division this study is aimed, to find out the administrative and regulatory system which land in Sarawak as a whole and in Samarahan division in particular. Development of land administration is a vast topic to study which lead to the complexity of the land administration.